The personal librarian - Benedict, Marie; Murray, Victoria Christopher (Berkley, 2021)
"The remarkable, little-known story of Belle da Costa Greene, J. P. Morgan's personal librarian-who became one of the most powerful women in New York despite the dangerous secret she kept in order to make her dreams come true, from New York Times bestselling author Marie Benedict and acclaimed author Victoria Christopher Murray. In her twenties, Belle da Costa Greene is hired by J. Pierpont Morgan to curate a collection of rare manuscripts, books, and artwork for his newly built Morgan Library. Belle becomes a fixture on the New York society scene and one of the most powerful people in the art and book world, known for her impeccable taste and shrewd negotiating for critical works as she helps build a world-class collection. But Belle has a secret, one she must protect at all costs. She was born not Belle da Costa Greene but Belle Marion Greener. She is the daughter of Richard Greener, the first Black graduate of Harvard and well-known advocate for equality. Belle's complexion isn't dark because of her alleged Portuguese heritage that lets her pass as white-her complexion is dark because she is African American. The Personal Librarian tells the story of an extraordinary woman, famous for her intellect, style, and wit, and shares the lengths she must go-for the protection of her family and her legacy-to preserve her carefully crafted white identity in the racist world in which she lives"--